Digitalisasi Perangkat Pembelajaran di Era EduTech dalam Pengembangan Platform JadiGuru sebagai Solusi Inovatif - Ratna Sari Dewi; Ester Debora Togatorop; Luhut Manurung; Chintiah Lafaezah Sihaloho; Angel Fortuna Dewi Sihombing (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to analyze the development and implementation of the JadiGuru platform as a solution for digitizing learning tools in the EduTech era. The main issues raised are teachers' limited access to learning tools tailored to their students' learning styles and the low utilization of digital technology in the learning process. This study used a descriptive qualitative approach with 12 informants, consisting of teachers, student teachers, and lecturers in the Makassar City educational environment. Data collection was conducted through direct observation and documentation studies, with data validation using source triangulation techniques. Data were analyzed using thematic analysis through the stages of data reduction, data presentation, and conclusion drawing. The results show that the JadiGuru platform provides 10–15 validated learning modules for high school students in grades X–XII in science and technology, mentor-based training features, discussion forums, and interactive learning media. All informants stated that this platform improves ease of access to learning tools and efficiency of teaching preparation time. The conclusion of this study is that JadiGuru has the potential to be an effective and adaptive digital solution to support the digitization of learning tools and the continuous improvement of teachers' professional competence.